Assessment of zonal distribution of methane on MSW landfills in northern regions for its usage in local power engineering - A.N. Chusov; V.I. Maslikov; D.V. Molodtsov; V.V. Zhazhkov; O.A. Riabuokhin (Инженерно-строительный журнал, 2015)
Municipal solid waste (MSW) landfills located in regions of Russia with low temperatures and relatively low rainfall averages are considered unpromising in terms of their biogas potential; however, these claims have not been substantiated. Assessment of the biogas potential of such landfills requires special field research for analyzing biogas composition and emission speed, which could define the processes taking place inside a landfill. We should note that the use of mathematical models that do not take into account the specifics of a particular landfill makes it impossible to get detailed and reliable information about its biogas potential. This work contains the results of research conducted for assessing the biogas potential of three municipal solid waste landfills located in various zones of the Northwestern Federal District with Atlantic continental and moderately continental climate. The research showed that biochemical processes of waste decomposition accompanied by the emission of biogas with high (50 vol% and above) methane content are possible even in areas with a relatively cold climate. This confirms the presence of the energy potential of these landfills, which can be used for the needs of heat, electricity and gas supply to the population, etc.